PD-1H Expression Associated With CD68 Macrophage Marker Confers an Immune-Activated Microenvironment and Favorable Overall Survival in Human Esophageal Squamous Cell Carcinoma - Chen, Yuangui; Feng, Rui; He, Bailin; Wang, Jun; Xian, Na; Huang, Gangxiong; Zhang, Qiuyu (Frontiers in Molecular Biosciences, 2021)
Esophageal squamous cell carcinoma (ESCC) is the most common type of esophageal carcinoma (EC) in China. Although the PD-1 inhibitor pembrolizumab has been approved to treat patients with EC, its therapeutic efficacy is limited. Thus, additional immunotherapeutic targets for EC treatment are needed. Programmed Death-1 Homolog (PD-1H) is a negative checkpoint regulator that inhibits antitumor immune responses. Here, PD-1H expression in 114 patients with ESCC was evaluated by immunohistochemistry. Next, 12 randomly selected tumor tissue sections were used to assess the colocalization of PD-1H protein and multiple immune markers by multiplex immunohistochemistry. Our results demonstrated that PD-1H was expressed at high frequency in ESCC tumor tissues (85.1%). PD-1H protein was predominantly expressed in CD68+ tumor-associated macrophages and expressed at low levels in CD4+ T cells and CD8+ T cells in ESCC tumor tissues. Furthermore, based on ESCC data in The Cancer Genome Atlas (TCGA), the gene expression levels of PD-1H were positively associated with the infiltration levels of immune-activated cells especially CD8+ cytotoxic T cells. In contrast, the gene expression levels of PD-1H were negatively correlated with myeloid-derived suppressor cells (MDSCs). Importantly, PD-1H expression in tumor sites was significantly correlated with favorable overall survival in patients with ESCC. Collectively, our findings first provided direct information on the PD-1H expression pattern and distribution in ESCC, and positive correlation of PD-1H expression with overall survival suggested PD-1H expression levels could be a significant prognostic indicator for patients with ESCC. Future studies need to explore the immunoregulatory of PD-1H in the tumor microenvironment of ESCC.